2004
DOI: 10.1099/jmm.0.45697-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of phenotypic methods for methicillin resistance characterization in coagulase-negative staphylococci (CNS)

Abstract: Coagulase-negative staphylococci (CNS) are the major cause of nosocomial infections. Methicillinresistant strains are particularly important because they narrow therapeutic options. Detecting methicillin resistance among CNS has been a challenge for years. The objective of this study was to determine the accuracy of an agar screening test (0 . 6 and 4 ìg oxacillin ml À1 ), disc diffusion and the automated MicroScan system to characterize methicillin resistance among CNS. One hundred and seventy five strains we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 18 publications
3
20
0
Order By: Relevance
“…This gene was located in a novel SSCmec designated type XI (10). Resistance to oxacillin, without the mecA gene, may be due to either the overproduction or overexpression of penicillinase or alteration of other penicillinbinding proteins (2). With respect to the SCCmec typing, the results are comparable to the distribution of the SCCmec types among S. haemolyticus strains that appeared to be major reservoirs of type V (13,16).…”
supporting
confidence: 72%
“…This gene was located in a novel SSCmec designated type XI (10). Resistance to oxacillin, without the mecA gene, may be due to either the overproduction or overexpression of penicillinase or alteration of other penicillinbinding proteins (2). With respect to the SCCmec typing, the results are comparable to the distribution of the SCCmec types among S. haemolyticus strains that appeared to be major reservoirs of type V (13,16).…”
supporting
confidence: 72%
“…We evaluated a higher number of isolates of SCoNne than other studies performed in Brazil, and we found high rates of resistance to oxacillin by PCR (71%) in these isolates, though earlier studies also included isolates of S. epidermidis [26][27][28]. In our study, among the SCoNne isolates, 100 were identified as S. haemolyticus, with 91% presenting a mecAgene-positive PCR result.…”
Section: Discussionmentioning
confidence: 37%
“…Moreover, the resistance in S. epidermidis can be transferred to Staphylococcus aureus (15). mecA gene detection through PCR is the gold-standard method for detecting resistance to oxacillin in staphylococci [16]. Since hospital health-care staff are one of the major sources of infection transmission, the aim of this study was to evaluate the prevalence of slime formation, to detect the aap (as one of the major factors in biofilm formation) and mecA genes by molecular methods, as well as to characterize the relationship between slime production and antibiotic resistance in S. epidermidis from hospital workers.…”
Section: Introductionmentioning
confidence: 99%